Prognostic Significance of POLE Exonuclease Domain Mutations in High-Grade Endometrioid Endometrial Cancer on Survival and Recurrence: A Subanalysis. Issue 5 (June 2016) - Billingsley, Caroline C.; Cohn, David E.; Mutch, David G.; Hade, Erinn M.; Goodfellow, Paul J.
Abstract : Objective: POLE mutations in high-grade endometrioid endometrial cancer (EEC) have been associated with improved survival. We sought to investigate the prevalence of POLE tumor mutation and its prognostic significance on outcomes and clinical applications in a subanalysis of women with high-grade EEC from a previously described cohort of 544 EEC patients in which POLE mutation status and survival outcomes were assessed. Methods: Polymerase chain reaction amplification and Sanger sequencing were used to test for POLE mutations in 72 tumors. Associations between POLE mutation, demographic and clinicopathologic features, and survival were investigated with Cox proportional hazard models. Results: POLE mutations were identified in 7 (9.7%) of 72 grade 3 EECs. No significant differences in the clinicopathologic features between those with POLE mutations and those without were identified. Adjusted for age, a decreased risk of recurrence was suggested in patients with a POLE mutation (adjusted hazard ratio, 0.37; 95% confidence interval, 0.09–1.55), as well as decreased risk of death (adjusted hazard ratio, 0.19; 95% confidence interval, 0.03–1.42). Conclusions: POLE mutations in tumors of women with grade 3 EEC are associated with a lower risk of recurrence and death, although not statistically significant because of high variability in these estimates. These findings, consistent with recently published combined analyses, support POLE mutation status as a noteworthy prognostic marker and may favor a change in the treatment of women with grade 3 EECs, particularly in those with early-stage disease, in which omission of adjuvant therapy and decreased surveillance could possibly be appropriate.